Hubungan Tingkat Kemandirian Berdasarkan Barthel Index dengan Hand Grip Strength pada Pasien Pasca Stroke - Dessy Carmelia Nurhadana; Shaura Ladayna Isma (Jurnal Riset Multidisiplin Edukasi, 2026)
Background: Motor function disorder in post-stroke patients causes muscle weakness that significantly impacts independence in activities of daily living (ADL). Hand grip strength measurement is a simple and objective parameter that reflects the overall neuromotor status of patients. In medical rehabilitation for patients, understanding the relationship between hand grip strength and Barthel Index independence level is crucial as it can facilitate early identification of patient's functional prognosis, ease rehabilitation progress monitoring, guide realistic goal setting, and provide rapid indicators for intervention effectiveness evaluation. However, the concrete relationship between these two parameters has not been extensively studied in local populations. Objective: To analyze the correlation between independence level based on Barthel Index and hand grip strength in post-stroke patients in chronic phase. Methods: This study employed a cross-sectional study design with 12 chronic phase stroke patients (onset 1-3 years). Independence level was measured using Barthel Index and hand grip strength was measured using a hydraulic hand dynamometer on the affected side. Analysis used Pearson correlation with α = 0.05. Results: There was a very strong positive and significant correlation between Barthel Index and hand grip strength (r = 0.9377; p < 0.0001), with R² = 0.8793. This indicates that 87.93% of the variation in hand grip strength can be explained by Barthel Index independence level. Conclusion: Hand grip strength is a very good predictor for daily independence level (ADL) in chronic stroke patients. Hand grip strength measurement can be integrated into routine assessment as a rapid and accurate screening tool.